The potential impact of new diagnostic criteria on the frequency of gestational diabetes mellitus in Sweden. (9th August 2013) - Claesson, Rickard; Ekelund, Magnus; Berntorp, Kerstin
Abstract The International Association of Diabetes and Pregnancy Study Groups (IADPSG) has suggested new diagnostic criteria for gestational diabetes mellitus. Many centers in Europe still use the World Health Organization (WHO) criteria. In southern Sweden we use the 2‐h threshold of the European Association for the Study of Diabetes criteria based on universal screening with a 75‐g oral glucose tolerance test. We have retrospectively scrutinized oral glucose tolerance tests in a subset of 174 women included in a previous study, diagnosed with gestational diabetes mellitus 1996–1999. A complete repeat oral glucose tolerance test was performed directly after diagnosis in 120 women. When applying the current Swedish criteria, and the IADPSG and the WHO criteria to the material, gestational diabetes mellitus was confirmed in 67% (80/120), 84% (101/120), and 80% (96/120), respectively. Hence, 26% (101/80) more women were identified by the IADPSG criteria and 20% (96/80) more women by the WHO criteria, compared with the criteria presently in use.